Effects of paeonol on the expression of NF-κB pathways in human umbilical veins endothelial cells induced by homocysteine (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to investigate the effects of paeonol on the expression of NF-κB pathway induced by homocysteine. After Human umbilical vein endothelial cells exposed to homocysteine for 24 hours,  paeonol (0.15-0.6 mmol/L) improved the cell viability (p